Geographic Information System Mapping of Essential Oil Producing Plants in Bangkalan Regency using K-Means Clustering - Nur, Achmad Zain; Jauhari, Achmad (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2024)
Essential oil is one of the high foreign exchange earning export commodities for Indonesia. Unfortunately, the high world market demand for essential oils has not been fully supplied by Indonesia. In Indonesia, essential oils generally come from farmers who have relatively small land and are then processed using simple distillation equipment. The same thing also happened in Kab. Bangkalan, Madura. This condition is the main reason why Indonesia's essential oil production is not optimal. To find out the distribution potential of essential oil-producing plants in Bangkalan Regency, it is necessary to have a step in building a system that can group the distribution areas of essential oil-producing plants, for this we need a clustering method. This study uses the K-Means Clustering method and uses the Euclidean algorithm to group the distribution areas of essential oil-producing plants, especially in Bangkalan Regency, so that later they can be identified based on clusters and displayed in visual form, namely in the form of digital maps using the Geographic Information System (GIS) application. Therefore, it is hoped that this research will be able to find out the distribution area of essential oil-producing plants in order to make it easier for local governments to monitor the potential of essential oil-producing areas in Bangkalan Regency.